Risalat/nabuwwat: current & eternal relevance - Gilani, Sayyid Muhammad Yunus (2015)
The human science or the human generated “knowledge” especially the physical science, through its methods of observation, experimentation and inferencing, in its study of the physical matter may be exact and accurate but not error-free, No doubt it is the natural science that has carried man to the moon, but it has not succeeded so far even in mastering thoroughly the mysteries of the human existence. Granted that the physical world/matter needs to be studied using the methodology of physical/natural science for want of any other sure method of studying the nature, matter and the material world. As regards the ultimate problems which comprehend within themselves the entire universe it would be extremely unscientific to expect their sure and accurate solutions from physical science. To know transcendental Reality and the ultimate truth, likewise the speculative human knowledge or philosophy, based on mere and share reason, is not capable of giving accurate answers to our ultimate questions . The philosophical answers have been best approximations in the nature of partial truths or in most instances “conjectures”. The sure and infallible source (and method of gaining) of knowledge (especially the metaphysical, transcendental and the ultimate) and guidance is the wahyu (revelation). The (divine) revealed knowledge gives direction and orientation to the physical and rational sciences as well and makes every thing meaningful and purposeful which otherwise could and would be misdirected and meaningless. The nabawi wahyu is revelation of the ultimate truth, and source of guidance and infallible knowledge. It leads us on the way and path of the Truth. It affirms the existence and implications of God ,the only All-Powerful (Omnipotent), All- knowing (Omniscient) and Omnipresent. And He not only possesses that knowledge but has also revealed to humanity the correct guidance on the ultimate and intricate problems which defy correct and sure solution by means of (mere human) senses, ordinary experience and reason. The divine Revelation has been communicated to us from time to time through the nabis /rasuls. Those Spiritual Luminaries, the chosen Messengers of our Creator included men like Adam, Ibrahim, Musa, Isa etc. the last among them being Muhammad (Divine Peace and Blessing be with him and all other Messengers of Allah swt). Man with limitations of his natural and philosophical sciences is eternally in need of the divine guidance and connection which is available in revealed guidance & knowledge of risalah . The rasul, an infallible divinely protected bashar, himself an epitome of virtues stands as model for human conduct at different levels.